Inovasi Mie Kremes Dengan Pemanfaatan Sawi Hijau Dan Daun Kersen - Musyaffa Rafi Hidayat; Ita Fatkhur Romadhoni; Niken Purwidiani; Andika Kuncoro Widagdo (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Mie kremes is a food product made from wheat flour and liquid in the form of noodles and then processed by drying so that it can be consumed without further cooking process. Mie kremes in this study is a processed product made from noodles (flour, eggs, water, salt) mustard greens, and cherry leaves are processed by steaming and roasting techniques. Shaped pieces of noodles with a length of 1cm evenly, which functioned as a snack at any time. The purpose of this product is : 1) to determine the organoleptic properties that include shape, color, taste, texture; 2) to determine the nutritional content of Mie kremes sawi hijau dan daun kersen. This type of research is experimental. The data collection technique used was observation through 5 trained panelists and 5 semi-trained panelists assisted with assessment observation sheets 1-5. The independent variables in this study are mustard greens and cherry leaves, the dependent variables in this study are shape, color, taste and texture, and the control variables in this study are the type of equipment, raw materials, and manufacturing techniques. Data analysis in this study using independent simple T test. The results of this study showed: 1) there is no influence of shape, taste and texture; 2) there is an influence of color on the product Mie kremes; it has a nutritional content of carbohydrates 77.50%, protein 11.05%, fat 6.09%, fiber 3.36%, water 2.01 %, antioxidants 31.2%, flavonoids 11.525%.